Association Between lncRNA HULC rs7763881 Polymorphism and Gastric Cancer Risk - Hong JH (Pharmacogenomics and Personalized Medicine, 2020)
Jang Hee Hong,1,2,* Eun-Heui Jin,3,* In Ae Chang,1 Hyojin Kang,1 Sang-Il Lee,4 Jae Kyu Sung5 1Clinical Trials Center, Chungnam National University Hospital, Daejeon, Republic of Korea; 2Department of Pharmacology, Chungnam National University College of Medicine, Daejeon, Republic of Korea; 3Research Institute for Medical Sciences, Chungnam National University College of Medicine, Daejeon, Republic of Korea; 4Department of Surgery, Chungnam National University Hospital, Chungnam National University College of Medicine, Daejeon, Republic of Korea; 5Department of Internal Medicine, Chungnam National University Hospital, Chungnam National University College of Medicine, Daejeon, Republic of Korea*These authors contributed equally to this workCorrespondence: Jae Kyu Sung; Sang-Il LeeDepartment of Internal Medicine, Chungnam National University Hospital, Chungnam National University College of Medicine, Daejeon, 35015, Republic of Korea; Department of Surgery, Chungnam National University Hospital, Chungnam National University College of Medicine, Daejeon 35015, Republic of KoreaTel +82-42-280-7186; +82-42-280-7180Fax +82-42-254-4553Email jksung69@gmail.com; mr231@cnuh.co.krPurpose: Gastric cancer (GC) is one of the most common cancers in the world. Recently, several studies have suggested that single-nucleotide polymorphisms (SNPs) of long noncoding RNA (lncRNA) are associated with GC risk. However, the association of the lncRNA highly upregulated in liver cancer (HULC) SNP with GC risk is not yet known. The aims of this study were to evaluate the association between HULC rs7763881 SNP and the risk of GC and GC subgroups via a case–control study.Patients and Methods: rs7763881 was genotyped using TaqMan genotyping assay with 459 GC patients and 379 controls.Results: A significant association between HULC rs7763881 SNP and GC risk was not found. However, after adjustment for age and gender, the rs7763881 recessive model (CC) showed a significant association with an increased GC risk in the undifferentiated (odds ratio (OR) = 1.85, 95% confidence interval (CI) = 1.17– 2.94, P = 0.009), diffuse-type GC (OR = 1.72, 95% CI = 1.05– 2.82, P = 0.033), LNM-positive (OR = 2.02, 95% CI = 1.24– 3.27, P = 0.004), T3/T4 (OR = 1.75, 95% CI = 1.05– 2.91, P = 0.032), and tumor stage III (OR = 2.01, 95% CI = 1.17– 3.45, P = 0.011) subgroups when compared to the rs7763881 combined genotypes (AA+AC). Furthermore, after adjusting for age and gender, the rs7763881 additive model (CC) indicated a significantly higher GC risk than rs7763881 AA genotype in the undifferentiated (OR = 1.96, 95% CI = 1.15– 3.32, P = 0.013), diffuse-type GC (OR = 2.08, 95% CI = 1.23– 3.52, P = 0.004), and LNM-positive (OR = 2.00, 95% CI = 1.14– 3.49, P = 0.016) subgroups.Conclusion: Our findings suggest that the HULC rs7763881 SNP is associated with increased susceptibility to GC. However, further studies are required to validate our results in large populations as well as different ethnic groups.Keywords: lncRNA, HULC, gastric cancer, polymorphism